Optimization of the use of Betterave (Beta Vulgaris) for the Production of Green Energy (Global Journal of Science Frontier Research, 2017)
This work aimed to conduct optimization method of ethanol production from using beet. To attain this objective, we propose to produce the distillation energy through biogas, and fertilizer for the culture of beet. We carried out some tests by using samples of red beets. These samples were subjected to fermentation, distillation with Vigreux column and methanization. The red beet was, a grinder, juice extractor, fermenters, fresh yeast, water, distillation device with a Vigreux column, two batch digesters, a balance and graduated containers. During the tests 376 mL of ethanol, 31 L of biogas and fertilizer evaluated at 1 KWh were obtained. The energy efficiency of production with this method stood at 58, 54 %. This discovery could be a solution to energy problems of many regions, an alternative to fossil energy while being a source of fertilizer. The proposed system does not reject waste: the carbon cycle and even that of nitrogen is closed. It is less costly and easy to put in place. He is environment friendly and has a good energetic performance.
Keywords: beet; fermentation; distillation; biogas; ethanol; fertilizer